1999
DOI: 10.1063/1.477930
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio calculation of the frequency-dependent interaction induced hyperpolarizability of Ar2

Abstract: Articles you may be interested inAb initio study of interaction-induced NMR shielding constants in mixed rare gas dimers J. Chem. Phys. 126, 074303 (2007); 10.1063/1.2446955Frequency-dependent hyperpolarizabilities of the Ne, Ar, and Kr atoms using the approximate coupled cluster triples model CC3The effect of intermolecular interactions on the electric properties of helium and argon. II. The dielectric, refractivity, Kerr, and hyperpolarizability second virial coefficientsThe effect of intermolecular interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 72 publications
1
23
0
Order By: Relevance
“…Its frequency dependence can be written as a power series of !. Truncation at the second-order term yields [30,31] A. Baranowska-L À a¸czkowska et al…”
Section: Theorymentioning
confidence: 98%
See 1 more Smart Citation
“…Its frequency dependence can be written as a power series of !. Truncation at the second-order term yields [30,31] A. Baranowska-L À a¸czkowska et al…”
Section: Theorymentioning
confidence: 98%
“…This is a formidable task which has been tackled to date only for two-body systems [31,[34][35][36] and will not be attempted here. B (T ) and B R (!, T ) are the secondorder expansion coefficients of the power series expansions in the density of the Clausius-Mossotti function [30,31,[37][38][39][40] …”
Section: Theorymentioning
confidence: 99%
“…This requires the determination of second and higher virial coefficients for the optical properties under investigation. In a previous article 7 we reported interaction in-duced polarizabilities and hyperpolarizabilities for the Ar 2 van der Waals complex for a range of internuclear distances. The frequency-dependence of the properties was accounted for through the expansion in the frequency arguments in terms of Cauchy moments and hyperpolarizability dispersion coefficients.…”
Section: Introductionmentioning
confidence: 95%
“…To reduce the computational costs of the calculations we follow the approach devised in Ref. 7 and expand ⌬␣(Ϫ;) and ⌬␥ ʈ ( 0 ; 1 , 2 , 3 ) as power series in the frequency arguments truncated to second order, i.e. after the lowest-order dispersion contribution, ⌬␣͑Ϫ; ͒ϭ⌬␣ϩ 2 ⌬S͑Ϫ4 ͒ϩO͑ 4 ͒, ͑1͒…”
Section: Computational Detailsmentioning
confidence: 99%
“…Extensive theoretical investigations have found that sufficiently high levels of theory, [21][22][23][24][25][26][27][28] combined with large basis sets 21,27-37 with bond functions, 21,27,38 -43 and counterpoise correction 21,27,28 are sufficient to accurately characterize the dimer interactions. At this time, such rigor is prohibitively time consuming ͑and less straightforward͒ to apply to larger vdW clusters in a practical way.…”
Section: Introductionmentioning
confidence: 99%